Kinerja Keuangan Dan Good Corporate Governance Terhadap Financial Distress - Godnevlyn, Valencya Blesscha; Tjhai, Fung Jin (Media Bisnis, 2025)
The purpose of this research is to obtain empirical evidence about the effect of leverage, profitability, liquidity, sales growth, managerial ownership, institutional ownership, and intellectual capital on financial distress. This research sample consists of data from 75 companies operating in the cyclical and non-cyclical consumer sectors listed in Indonesia Stock Exchange (IDX) for the period 2020 - 2022. This research uses purposive sampling and using multiple regression analysis. The research results show that leverage, profitability, and liquidity have effect on financial distress. Leverage with high level of debt affecting the company’s inability to pay debts in the future, thereby increasing the risk of financial distress. High profitability is characterized by high expenses and increasing the risk of financial distress. High liquidity may increase the risk of financial distress if the company's current assets are greater than its fixed assets. Sales growth, managerial ownership, institutional ownership, and intellectual capital had no effect to financial distress.